Pengaruh modifikasi media S terhadap produksi spora, viabilitas, dan patogenisitas jamur agensia hayati - Mu’arif, Imam Al; Fitriana, Yuyun; Suharjo, Radix; Swibawa, I Gede (Universitas Lampung, 2024)
Biological control fungi can be stored and produced in the form of spores on a specific medium. For mass production, a large quantity of spores is required in a short amount of time. This study aims to determine the effect of medium S on the sporulation, spore viability, and pathogenicity of the fungi Beauveria bassiana, Metarhizium flavoviride, Purpureocillium lilacinum, and Trichoderma asperellum. There were two sets of experiments in this study. The first experiment tested the growth ability of fungal isolates on modified medium S in vitro. The second experiment tested the viability of the fungi that had been grown on the medium used in the previous experiment. The results showed that the type of fungus and the type of medium affected growth and spore production but did not influence spore viability. Among the biological agents, there appears to be mutual inhibition, though this inhibition does not seem to affect their ability to cause the death of the test insects. The consortium of biological agents resulted in a higher mortality rate of the test insects compared to single-agent applications.